2019
DOI: 10.18537/mskn.10.02.04
|View full text |Cite
|
Sign up to set email alerts
|

Bullying y cyberbullying escolar en niños y jóvenes adolescentes: un estudio de caso

Abstract: Fecha de recepción: 17 de mayo de 2019-Fecha de aceptación: 2 de octubre de 2019 RESUMEN El objetivo de la investigación fue identificar la incidencia de bullying y cyberbullying en 983 estudiantes de 10 a 15 años de edad, del sexto al décimo año de EGB, pertenecientes a cinco instituciones educativas de la ciudad de Cuenca, para lo cual se cruzaron las variables de bullying y cyberbullying con la edad, el sexo y nivel educativo de los estudiantes encuestados, visualizando la implicación de los protagonistas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
2
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
1
1
2
5
Order By: Relevance
“…In contrast, the results of the study by Górriz et al [21] show significant findings with a higher presence of males in the victim role and females in the aggressor role. Thus, other research suggests that boys and male adolescents are more involved in the roles of "victims" and "no victim-aggress", which does not align with the results of this study, where a higher percentage of girls are observed in these categories compared to boys [40].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, the results of the study by Górriz et al [21] show significant findings with a higher presence of males in the victim role and females in the aggressor role. Thus, other research suggests that boys and male adolescents are more involved in the roles of "victims" and "no victim-aggress", which does not align with the results of this study, where a higher percentage of girls are observed in these categories compared to boys [40].…”
Section: Discussioncontrasting
confidence: 99%
“…The results showed that physical bullying does occurs more in the male gender, while verbal bullying and social exclusion prevail in the female gender. Similar results were found by Ordóñez and Prado-Cabrera [34], showing that the role of victimised aggressor in both bullying and cyberbullying cases presents a higher level of involvement at the male gender level.…”
Section: Gender and Bullying Prevalence: How They Relatesupporting
confidence: 86%
“…The students' level of conflict and their perceptions were verified before and after applying the programme, but no differences were showed, affirming hypothesis 6 and 7. These results are contradictory to those obtained by Chocarro and Garaigordobil [31], Ruiz et al [33] and Ordóñez and Prado-Cabrera [34]. Perhaps the reason for such results was due to the justification provided by Navarro et al (2016) when they affirm that the problem does not lie in gender, but in gender identity.…”
Section: Discussionmentioning
confidence: 70%
“…Se da a causa de baja autoestima y es más predominante en las mujeres en el rol de víctima (Garaigordobil & Machimbarrena, 2019;Jordán et al, 2022). Es considerado un tipo de maltrato emocional que consiste en causar aflicción a través del internet, haciendo uso de los dispositivos móviles que funcionan con éste, a través de mensajes insultantes u ofensivos, imágenes humillantes o con sentido de burla, comentarios, habladurías y falsos rumores (Cortés, 2020;Ordóñez & Prado-Cabrera, 2019;Verdejo et al, 2015).…”
Section: Ciberbullyingunclassified